GRPR antagonist protects from drug‐induced liver injury by impairing neutrophil chemotaxis and motility. Issue 4 (7th April 2017) - Czepielewski, Rafael S.; Jaeger, Natália; Marques, Pedro E.; Antunes, Maísa M.; Rigo, Maurício M.; Alvarenga, Débora M.; Pereira, Rafaela V.; da Silva, Rodrigo D.; Lopes, Tiago G.; da Silva, Vinícius D.; Porto, Bárbara N.; Menezes, Gustavo B.; et al.
Abstract : Drug‐induced liver injury is expanded by neutrophil recruitment. Here, we describe that a GRPR antagonist protects from extended liver damage by reducing neutrophil activation and motility. An unexpected interaction between GRPR antagonist and CXCR2 competes for the binding site of CXCL8, preventing neutrophil chemotaxis. Abstract : Drug‐induced liver injury (DILI) is a major cause of acute liver failure (ALF), where hepatocyte necrotic products trigger liver inflammation, release of CXC chemokine receptor 2 (CXCR2) ligands (IL‐8) and other neutrophil chemotactic molecules. Liver infiltration by neutrophils is a major cause of the life‐threatening tissue damage that ensues. A GRPR (gastrin‐releasing peptide receptor) antagonist impairs IL‐8‐induced neutrophil chemotaxis in vitro. We investigated its potential to reduce acetaminophen‐induced ALF, neutrophil migration, and mechanisms underlying this phenomenon. We found that acetaminophen‐overdosed mice treated with GRPR antagonist had reduced DILI and neutrophil infiltration in the liver. Intravital imaging and cell tracking analysis revealed reduced neutrophil mobility within the liver. Surprisingly, GRPR antagonist inhibited CXCL2‐induced migration in vivo, decreasing neutrophil activation through CD11b and CD62L modulation. Additionally, this compound decreased CXCL8‐driven neutrophil chemotaxis in vitro independently of CXCR2 internalization, induced activation of MAPKs (p38 and ERK1/2) and downregulation of neutrophil adhesion molecules CD11b and CD66b. In silico analysis revealed direct binding of GRPR antagonist and CXCL8 to the same binding spot in CXCR2. These findings indicate a new potential use for GRPR antagonist for treatment of DILI through a mechanism involving adhesion molecule modulation and possible direct binding to CXCR2.